2020
DOI: 10.1371/journal.pone.0232798
|View full text |Cite
|
Sign up to set email alerts
|

Bright light therapy in the treatment of patients with bipolar disorder: A systematic review and meta-analysis

Abstract: The treatment of depressive symptoms of bipolar disorder (BD) has received increasing attention. Recently, some studies have shown that bright light therapy (BLT) seems to be useful for BD depression. This meta-analysis is intended to further elucidate the role of BLT in depressive symptoms in patients with BD. Register of Systematic Reviews PROSPERO: CRD 420191 33642.Randomized controlled trials and cohort studies were retrieved in PubMed, Cochrane Library, EMbase, Web of Science, CINHAL, CBM, CNKI, VIP, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 75 publications
(152 reference statements)
0
8
0
Order By: Relevance
“…A recent meta-analysis of 6 randomized controlled trials that examined the effects of bright light therapy versus placebo on bipolar depression failed to detect significant improvements in rates of remission for depressive episodes, improvements in depressive symptom scores, and rates of switching to manic episodes [ 26 ]. In contrast, a separate meta-analysis on the efficacy of bright light therapy that included five randomized controlled trials and seven cohort studies reported significant improvements in the severity of depressive symptoms for patients exposed to bright light therapy, especially for light intensities greater than 5000 lx [ 27 ].…”
Section: Circadian Disturbances In Bdmentioning
confidence: 99%
“…A recent meta-analysis of 6 randomized controlled trials that examined the effects of bright light therapy versus placebo on bipolar depression failed to detect significant improvements in rates of remission for depressive episodes, improvements in depressive symptom scores, and rates of switching to manic episodes [ 26 ]. In contrast, a separate meta-analysis on the efficacy of bright light therapy that included five randomized controlled trials and seven cohort studies reported significant improvements in the severity of depressive symptoms for patients exposed to bright light therapy, especially for light intensities greater than 5000 lx [ 27 ].…”
Section: Circadian Disturbances In Bdmentioning
confidence: 99%
“…It is also not clear how applicable these findings are to patients with bipolar disorder. The optimal mix of daylight and electric lighting for circadian entrainment needs to be clarified to increase understanding of bipolar disorder and suicide risk, and improve the efficacy of chronotherapeutic treatments (Geoffroy and Palagini 2021 ; Gottlieb et al 2019 ; Münch et al 2020 ; Wang et al 2020 ; Wirz-Justice and Benedetti 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been hypothesized that light therapy improves mood in SAD by resetting the circadian rhythms that were desynchronized due to the seasonal light deficiency [57]. Over the years, several trials and meta-analyses have extended the use of light to non-seasonal depression and demonstrated that light therapy can be proposed a first-line monotherapy not only for treating seasonal depression, but also non-seasonal depression [13,[58][59][60], both for unipolar disorders [11,13,59,61] and BD [12,[61][62][63][64]. These discoveries of the efficacy of light on mood disorder are not surprising, light is the most salient cue for entraining circadian rhythms [65] and a large number of studies demonstrated the involvement of biological rhythm abnormalities, both circadian and infradian ones, in seasonal and non-seasonal unipolar and bipolar disorder [19,[66][67][68][69].…”
Section: Parameters Influencing Light Mood Effectsmentioning
confidence: 99%